Yield Performance of Wheat Isolines with Different Dosages of the Short Arm of Rye Chromosome 1. (9th May 2014) - Maheepala, D. C.; Ehdaie, B.; Waines, J. G.
Abstract Translocations of the short arm of rye (Secale cereale L.) chromosome 1 (1RS) in wheat (Triticum aestivum L. cv. Pavon 76) are known to increase root biomass. Such an increase enhances water and nutrient uptake and may improve grain yield. Two greenhouse experiments and a field experiment were carried out at the University of California, Riverside, in 2012 and 2013 under well‐watered and terminal drought treatments to evaluate phenotypic characters associated with varying dosages of 1RS, including grain yield. The genotypes used were cultivar Pavon 76 (R0), Pavon 76/Pavon1RS.1AL (F1 hybrid) with a single dosage of 1RS (R1A), Pavon 1RS.1AL with two dosages of 1RS (R2A), Pavon 1RS.1DL (R2D) also with two dosages of 1RS and Pavon 1RS.1AL‐1RS.1DL (R4AD) with four dosages of 1RS. There was a significant positive correlation between number of dosages of 1RS and root biomass. However, no correlation was found between root biomass and grain yield per plant. Drought in the field experiment reduced grain yield significantly. Under well‐watered field conditions, grain yield of R2A (215.9 g plant−1) was significantly greater than those of R2D (191.8 g plant−1) and R4AD (161.7 g plant−1). Also, grain yield of R4AD was significantly less than those of F1, Pavon 76 and R2D under well‐watered conditions. Under drought field conditions, no significant differences were found among the genotypes for grain yield was found between F1 (14.7 g plant−1) and R4AD (12.4 g plant−1). Harvest index was significantly greater in well‐watered (44.2 %) than in drought (34.6 %) field conditions. On average, genotypes F1 (42.3 %) and R2A (40.6 %) had higher harvest index than R2D (38.3 %) and R4AD (35.5 %) in the field. Also, Pavon 76 (40.2) and R2D (38.3) had higher harvest index than R4AD. Drought tolerance was lowest for R4AD due to its relatively lower grain yield potential. In general, Pavon 1RS.1AL carrying two dosages of 1RS showed higher grain yield under wet treatments. Pavon 1RS.1AL‐1RS.1DL carrying four dosages of 1RS produced the largest shoot and root biomasses, but the least grain yield.